Adaptive numerical method algorithms for nonlinear viscous and bilinear oil damper models subjected to dynamic loading. Issue 113 (October 2018) - Akcelyan, Sarven; Lignos, Dimitrios G.; Hikino, Tsuyoshi
Abstract: Adaptive numerical method algorithms are presented for the numerical simulation of the hysteretic behaviour of nonlinear viscous and bilinear oil dampers within a finite element program for nonlinear dynamic analysis of frame structures under earthquake excitations. The adaptive algorithms are applicable for computing high-precision solutions for nonlinear viscous and bilinear oil dampers with valve relief that are typically represented mathematically with a nonlinear Maxwell model. The algorithms presented possess excellent convergence characteristics for viscous dampers with a wide range of velocity exponents and axial stiffness properties. The algorithms are implemented in an open source finite element software, and their applicability and computational efficiency is demonstrated through a number of validation examples with data that involve component experimentation as well as the utilization of full-scale shake table tests of a 5-story steel building equipped with nonlinear viscous and bilinear oil dampers. Highlights: Presents adaptive numerical algorithms for nonlinear viscous and bilinear oil dampers. Predict high-precision solutions and excellent convergence characteristics. Validated with full-scale component tests of viscous and oil dampers. Implemented in open source nonlinear frame analysis platform. Validated with full-scale shake table experiments of a 5-story frame building.